KRAS-G12C Mutation in One Real-Life and Three Population-Based Nordic Cohorts of Metastatic Colorectal Cancer - Osterlund, Emerik; Ristimäki, Ari; Kytölä, Soili; Kuopio, Teijo; Heervä, Eetu; Muhonen, Timo; Halonen, Päivi; Kallio, Raija; Soveri, Leena-Maija; Sundström, Jari; Keinänen, Mauri; Ålgars, Annika; et al. (Frontiers in Oncology, 2022)
Background KRAS mutations, present in over 40% of metastatic colorectal cancers (mCRC), are negative predictive factors for anti-EGFR therapy. Mutations in KRAS-G12C have a cysteine residue for which drugs have been developed. Published data on this specific mutation are conflicting, thus, we studied the frequency and clinical characteristics in a real-world and population-based setting. Methods Patients from three Nordic population-based cohorts and the real-life RAXO-study were combined. RAS and BRAF testing were performed in routine healthcare, except for one cohort. The dataset consisted of 2559 patients, of which 1871 could be accurately KRAS, NRAS, and BRAF-V600E classified. Demographics, treatments, and outcomes were compared with logistic regression. Overall survival (OS) was estimated with Kaplan-Meier and differences compared using Cox regression, adjusted for baseline factors. Results The KRAS-G12C frequency was 2-4% of all tested in the seven cohorts (mean 3%), and 4-8% of KRAS mutated tumors in the cohorts (mean 7%). “ Metastasectomies and/or ablations were performed more often (38% vs. 28%, p=0.040) and bevacizumab was added more often (any line 74% vs. 59%, p=0.007) to patients with KRAS-G12C vs. other KRAS mutated tumors, whereas chemotherapy was given to similar proportions. OS did not differ according to KRAS mutation, neither overall (adjusted HR 1.03; 95% CI 0.74-1.42, reference KRAS-G12C) nor within treatment groups defined as “systemic chemotherapy, alone or with biologics”, “metastasectomy and/or ablations”, or “best supportive care”. RAS&BRAF wild-type tumors (n=548) differed similarly to KRAS-G12C, as to other KRAS or NRAS (n=66) mutated tumors. Conclusions In these real-life and population-based cohorts there were no significant differences in patient characteristics, and outcomes between patients with KRAS-G12C tumors and those with other KRAS mutations. This contrasts to the results of most previous studies claiming differences in many aspects, often with worse outcomes for those with a KRAS-G12C mutation, however, not consistent. When specific drugs are developed, as for this mutation, differences in outcome will hopefully emerge.